Formation of diagnostics indicator base of the university scientific activity system - Kuzmin, Oleh; Melnyk, Olha; Zhuk, Liliya (Technology audit and production reserves, 2017)
The object of research is the indicators for the diagnosis of the state of the system of scientific activity of higher educational institutions (HEIs), including universities. Diagnostics of scientific activity today takes on special significance for the HEIs that are in a highly competitive environment in the market of educational and scientific services. During the research methods of expert evaluation, analysis and synthesis, logical generalization were used. A set of representative indicators reflecting the resource support of scientific activity, its effectiveness, and also characterize the stability, adaptability and reliability of the system are obtained. All indicators are grouped by the following subsystems: conducting research; training of highly qualified scientific personnel; maintenance of creative activity of participants of educational process; use of scientific results obtained in the educational process. The proposed set of indicators forms the basis for further interpretation of the state of the system of scientific activity of the university, obtaining a holistic view of the problems, shortcomings and threats to the implementation of scientific activity, and making informed management decisions. Proposals have been formulated to complement the forms of «Indicators of Scientific and Technical and Technological Activities of HEI» with additional indicators, in particular on the level of qualifications of the SSPW and the HEI scientific infrastructure, which provide more reliable data for diagnosing the HEI scientific activity. Interpretation of monitoring results and assessment of the state of the scientific activity system on the proposed indicators will allow to form an information array of data on existing problems, potential threats and risks in the field of scientific activity. And also in the future – to develop proposals to eliminate these problems, to prevent threats and risks.